Periodization method of physical exercise for obese people - Chikih, Chikih; Anggunadi, Angelica (Jurnal Keolahragaan, 2023)
During the COVID-19 pandemic, The Centers for Disease Control and Prevention CDC, stated that obesity prevalence increased by 52%. In Indonesia, the prevalence of obesity is 21.8%. Obesity triggers an increase in pro-inflammatory cytokines, which induces chronic inflammation both locally and systemically, which can cause health problems, such as cardiovascular disease, diabetes mellitus, metabolite syndrome, and an increased risk of infection. One of the components of obesity management is increasing physical activity. One of the domains of physical activity is exercise. Exercise with the appropriate frequency, duration, intensity, type, and periodization can influence cytokine modulation so that it can reduce systemic inflammation and increase physical fitness. This evidence-based case report (EBCR) aims to determine the type of exercise periodization in obesity management and its effect on health-related fitness. The process of searching for literature on EBCR uses the PRISMA method on 3 databases, namely: PubMed, EBSCOhost, and ProQuest. From the search results, it was found that the combination of endurance and strength training exercises with linear periodization 3 times a week, was found to be better in improving fitness in obese people. Linear periodization increases cardiopulmonary fitness with a relative mean difference of 17.8(0.3 to 35.3) %, maximal strength with 1 RM bench press and 1 RM leg press test also increased, and also reduce body fat percentage about 2.1(-4.8 to 0.5) %. Thus, the combination of strength and cardiorespiratory exercise with linear periodization gives a positive response to the components of health-related fitness in obese people.